Propylene-based resin composition and its uses
The propylene-based resin composition addresses moldability and whitening issues by combining specific copolymers and polymers, enhancing melt tension and flow rates to produce high-quality molded parts with improved tensile properties and resistance to whitening.
Patent Information
- Application Number
- JP2021043313
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-17
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2041-03-17
AI Technical Summary
Conventional propylene resin compositions suffer from insufficient whitening suppression and moldability during molding processes, particularly in blow molding and extrusion, with issues such as drawdown and neck-in, and inadequate melt tension.
A propylene-based resin composition comprising a propylene-ethylene-α-olefin copolymer, a propylene branched polymer, and a propylene polymer, with specific melt flow rates and melt tensions, ranging from 0.1 to 50 g/10 minutes and 5 to 300 mN, respectively, to enhance moldability and suppress whitening.
The composition achieves excellent moldability with moderate melting tension, resulting in molded bodies with improved tensile properties and whitening resistance.
Smart Images

Figure 0007627583000001 
Figure 0007627583000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a propylene-based resin composition, an adhesive resin composition, pellets, a molded article, a non-oriented film, a sheet, an injection molded article, a blow molded article, and an automobile part. [Background technology]
[0002] 2. Description of the Related Art In recent years, propylene-based polymers containing propylene as a main component have become known as soft polyolefin materials which are excellent in flexibility, heat resistance and transparency as well as environmental friendliness and hygienic properties.
[0003] At present, while the applications of propylene-based resin compositions containing such propylene-based polymers are expanding, conventional propylene-based resin compositions have a problem that the molded product is easily whitened (hereinafter also simply referred to as "whitening") during molding processing such as blow molding and stretching, or during secondary processing. In addition, for example, drawdown or necking is easily caused during molding such as blow molding or extrusion molding, and the moldability is insufficient. One index of the moldability is melt tension.
[0004] As a propylene-based resin composition capable of suppressing the whitening and having excellent moldability, Patent Documents 1 and 2 describe a propylene-based resin composition containing a propylene-based branched polymer having high melt tension. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-216207 A [Patent Document 2] JP 2019-85480 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, while the conventional propylene-based resin compositions described in Patent Documents 1 and 2 can suppress whitening to some extent, the degree of suppression is not sufficient, and there is room for improvement in terms of achieving both whitening suppression and moldability.
[0007] The present invention has been made in view of the above, and an object of the present invention is to provide a propylene-based resin composition that can suppress whitening of molded articles during molding or secondary processing, and has excellent molding processability and appropriate melt tension. [Means for solving the problem]
[0008] A configuration example of the present invention is as follows. In this specification, the numerical range "A to B" indicates A or more and B or less.
[0009] [1] A propylene-ethylene-α-olefin copolymer (A), A propylene-based branched polymer (B) other than the copolymer (A), A propylene-based polymer (C) other than the copolymer (A) and the polymer (B), A propylene-based resin composition comprising: The propylene-based resin composition has a melt flow rate (230° C., 2.16 kg load) of 0.1 to 50 g / 10 min; The melt tension (230°C) of the propylene-based resin composition is 5 to 300 mN. Propylene-based resin composition.
[0010] [2] With respect to 100% by mass of the total of the copolymer (A), the polymer (B) and the polymer (C), The content of the copolymer (A) is 1 to 40% by mass, The content of the polymer (B) is 0.5 to 40 mass %, The content of the polymer (C) is 20 to 98.5% by mass. The propylene-based resin composition according to [1].
[0011] [3] The propylene-based resin composition according to [1] or [2], wherein the polymer (B) has a melt flow rate (230°C, 2.16 kg load) of 0.5 g / 10 min or more.
[0012] [4] The copolymer (A) contains a structural unit (i) derived from propylene, a structural unit (ii) derived from ethylene, and a structural unit (iii) derived from an α-olefin having 4 to 20 carbon atoms, and relative to the total of these 100 mol %, The content of the structural unit (i) is 50 to 92 mol %, The content of the structural unit (ii) is 5 to 20 mol %, The content of the structural unit (iii) is 3 to 30 mol %. The propylene-based resin composition according to any one of [1] to [3].
[0013] [5] The propylene-based resin composition according to any one of [1] to [4], wherein the copolymer (A) has a melting point of less than 100°C or no melting peak is observed as measured by a differential scanning calorimeter.
[0014] [6] The propylene-based resin composition according to any one of [1] to [5], wherein the copolymer (A) is a propylene-ethylene-1-butene copolymer.
[0015] [7] The propylene-based resin composition according to any one of [1] to [6], wherein the polymer (C) is a homopolypropylene or a random propylene copolymer.
[0016] [8] An adhesive resin composition comprising the propylene-based resin composition according to any one of [1] to [7]. [9] A pellet comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8].
[10] A molded article comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8].
[11] A non-stretched film comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8].
[12] A sheet comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8].
[13] An injection-molded article comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8].
[14] A blow molded article comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8].
[15] An automobile part selected from an interior part and an exterior part, comprising the propylene-based resin composition according to any one of [1] to [7] or the adhesive resin composition according to [8]. Effect of the Invention
[0017] According to the present invention, it is possible to provide a propylene-based resin composition which can suppress whitening, has excellent moldability, and has an appropriate melt tension. Moreover, the propylene-based resin composition according to the present invention has excellent moldability, and from such a propylene-based resin composition having excellent moldability, a molded article having excellent tensile properties and whitening resistance can be formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] <Propylene-based resin composition> The propylene-based resin composition according to the present invention (hereinafter also referred to as "the composition") contains a propylene-ethylene-α-olefin copolymer (A) (hereinafter also referred to simply as "copolymer (A)"), a propylene-based branched polymer (B) (hereinafter also referred to simply as "polymer (B)") other than the copolymer (A), and a propylene-based polymer (C) (hereinafter also referred to simply as "polymer (C)") other than the copolymer (A) and polymer (B), The composition has a melt flow rate (230°C, 2.16 kg load) of 0.1 to 50 g / 10 min and a melt tension of 5 to 300 mN.
[0019] The melt flow rate (MFR) of the present composition is 0.1 g / 10 min or more, preferably 0.3 g / 10 min or more, more preferably 0.5 g / 10 min or more, and is 50 g / 10 min or less, preferably 49 g / 10 min or less, more preferably 48 g / 10 min or less. When the MFR is within the above range, the moldability, mechanical strength, and whitening resistance are well balanced and excellent. If the MFR is below the lower limit of the above range, the flowability will be low and molding will tend to be difficult, whereas if the MFR is above the upper limit of the above range, the mechanical strength may decrease. The MFR is a value measured at 230° C. under a load of 2.16 kg in accordance with ASTM D1238.
[0020] The melt tension of the present composition is 5 mN or more, preferably 5.5 mN or more, more preferably 6 mN or more, and is 300 mN or less, preferably 290 mN or less, more preferably 280 mN or less. When the melt tension is within the above range, drawdown and the like are unlikely to occur, the molding processability is excellent, and the resin is also unlikely to break even during high-speed molding. Specifically, the melt tension is measured by the method described in the following examples.
[0021] The tensile modulus of the present composition is preferably 200 to 2000 MPa, more preferably 250 to 1980 MPa, and further preferably 300 to 1960 MPa. Specifically, the tensile modulus is measured by the method described in the examples below.
[0022] The tensile stress at break of the present composition is preferably 5 MPa or more, more preferably 10 MPa or more, and even more preferably 15 MPa or more. Specifically, the tensile breaking stress is measured by the method described in the examples below.
[0023] The composition has a Shore D hardness (instantaneous value) of preferably 30-90, more preferably 32-88, and further preferably 34-86. The Shore D hardness (instantaneous value) is specifically measured by the method described in the following Examples.
[0024] When the tensile modulus of elasticity and the tensile stress at break are within the above ranges, and the Shore D hardness is also within the above ranges, it is possible to obtain a composition (molded article) that is excellent in balance between flexibility and mechanical strength such as tensile strength.
[0025] <Propylene-ethylene-α-olefin copolymer (A)> The copolymer (A) is not particularly limited as long as it is a copolymer of propylene, ethylene, and an α-olefin, but is preferably a random copolymer. By using the copolymer (A), whitening can be suppressed, and a molded article having excellent flexibility and low elution amount of components into oil or the like can be easily formed. The copolymer (A) contained in the present composition may be one type or two or more types.
[0026] The α-olefin is not particularly limited, but is preferably an α-olefin having 4 to 20 carbon atoms. Examples of the α-olefin include 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. Among these, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene are preferred, and 1-butene is more preferred. The α-olefin may be used in two or more kinds, but preferably in one kind.
[0027] The copolymer (A) preferably contains a structural unit (i) derived from propylene, a structural unit (ii) derived from ethylene, and a structural unit (iii) derived from an α-olefin having 4 to 20 carbon atoms.
[0028] The content of the structural unit (i) is preferably 50 mol% or more, more preferably 55 mol% or more, even more preferably 60 mol% or more, particularly preferably 61 mol% or more, and is preferably 92 mol% or less, more preferably 90 mol% or less, even more preferably 88 mol% or less, still more preferably 86 mol% or less, particularly preferably 85 mol% or less. The content of the structural unit (ii) is preferably 5 mol% or more, more preferably 6 mol% or more, and even more preferably 8 mol% or more, and is preferably 20 mol% or less, more preferably 19 mol% or less, and even more preferably 18 mol% or less. The content of the structural unit (iii) is preferably 3 mol % or more, more preferably 5 mol % or more, and preferably 30 mol % or less, more preferably 29 mol % or less, and even more preferably 28 mol % or less. Furthermore, the total content of the structural units (ii) and (iii) relative to 100 mol % of the total of the structural units (i) to (iii) is preferably 10 to 45 mol %, and more preferably 12 to 45 mol %. The content of each of the structural units (i) to (iii) is the content when the total of the structural units (i) to (iii) is taken as 100 mol %.
[0029] When the contents of the structural units (i) to (iii) are within the above ranges, the transparency, flexibility, and mechanical strength tend to be excellent and well-balanced, and the compatibility with the polymer (B) and the polymer (C) tends to be good. The content of the structural units (i) to (iii) is 13 It can be measured by C-NMR, specifically, the method described in JP-A-2007-186664.
[0030] The MFR of the copolymer (A) is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, even more preferably 0.5 g / 10 min or more, and is preferably 35 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, still more preferably 5 g / 10 min or less, and particularly preferably 3 g / 10 min or less. When the MFR is within the above range, the moldability and mechanical strength are well balanced. If the MFR is below the lower limit of the above range, the fluidity will be low, making molding difficult, and compatibility with other resins will tend to decrease, whereas if the MFR is above the upper limit of the above range, sticky components will tend to increase. The MFR is a value measured at 230° C. under a load of 2.16 kg in accordance with ASTM D1238.
[0031] The melting point Tm of the copolymer (A) measured by DSC is preferably less than 100°C or no melting peak is observed. If a melting peak is observed, Tm is more preferably 90°C or lower, and even more preferably 85°C or lower. When Tm is within the above range, or when no melting peak is observed, a molded article having excellent flexibility can be easily formed. Specifically, the melting peak is measured by the method described in the following examples, where Tm refers to the temperature at the peak apex of the melting peak, and "no melting peak is observed" refers to no crystal melting peak having a crystal melting heat of 1 J / g or more observed in the range of -100 to 200°C. When two or more melting peaks are observed, the lowest temperature among the peak apex temperatures of these peaks is the melting point.
[0032] When the melting peak is observed, the heat of fusion (ΔH), which is the integrated value of the peak, is preferably 10 J / g or more, more preferably 20 J / g or more, and preferably 50 J / g or less, more preferably 45 J / g or less, and even more preferably 40 J / g or less. When ΔH is within the above range, flexibility and low stickiness are well balanced.
[0033] The glass transition temperature Tg of the copolymer (A) is preferably 0° C. or lower, more preferably −10° C. or lower, and further preferably −20° C. or lower. When the Tg is within the above range, a molded article having excellent cold resistance and low-temperature properties can be easily formed. Specifically, the Tg is measured by the method described in the Examples below.
[0034] The intrinsic viscosity [η] of the copolymer (A) measured in decalin at 135° C. is preferably from 0.01 to 10 dl / g, more preferably from 0.05 to 10 dl / g. When the intrinsic viscosity [η] is within the above range, a molded article having excellent properties such as heat aging resistance, low-temperature properties, and mechanical strength can be easily formed.
[0035] The tensile modulus of the copolymer (A) is preferably 0.5 MPa or more, more preferably 1 MPa or more, and is preferably 200 MPa or less, more preferably 150 MPa or less. When the tensile modulus is within the above range, a molded article having superior flexibility can be easily obtained. Specifically, the tensile modulus is measured by the method described in the examples below.
[0036] The copolymer (A) has a Shore A hardness (instantaneous value) of preferably 20-97, and more preferably 30-97. In particular, the copolymer (A) having a tensile modulus of 10 MPa or less has a Shore A hardness (instantaneous value) of preferably 20 or more, more preferably 30 or more, and preferably 50 or less, more preferably 45 or less. Moreover, the copolymer (A) having a tensile modulus of elasticity exceeding 10 MPa preferably has a Shore A hardness (instantaneous value) of 48 or more, more preferably 50 or more, and preferably 97 or less. When the Shore A hardness (instantaneous value) is within the above range, a molded product having superior flexibility can be easily obtained. The Shore A hardness (instantaneous value) is a value measured by the method described in the following examples.
[0037] The method for producing the copolymer (A) is not particularly limited, but it can be produced by copolymerizing an olefin in the presence of a known catalyst, for example, a catalyst mainly composed of a solid titanium component and an organometallic compound, or a metallocene catalyst using a metallocene compound as one of the catalyst components.Preferably, as described later, it is obtained by copolymerizing propylene, ethylene and α-olefin in the presence of a metallocene catalyst, and the catalyst can be, for example, the catalyst described in International Publication No. 2004 / 087775 or JP-A No. 2007-186664.
[0038] The content of copolymer (A) in the present composition is preferably 1 mass% or more, more preferably 2 mass% or more, and even more preferably 5 mass% or more, preferably 40 mass% or less, more preferably 38 mass% or less, and even more preferably 35 mass% or less, relative to 100 mass% in total of copolymer (A), polymer (B) and polymer (C). When the content of the copolymer (A) is within the above range, a molded product having excellent transparency, mechanical properties (flexibility, rigidity, etc.) and whitening resistance can be easily formed.
[0039] When two or more kinds of copolymers (A) are used, the content of the copolymer (A) refers to the total amount of these two or more kinds of copolymers (A) contained in the present composition. The same applies when two or more kinds of other components such as polymer (B) and polymer (C) are used.
[0040] <Propylene-based branched polymer (B)> The polymer (B) is a polymer having a branched chain (for example, a long-chain branched chain) and a structural unit derived from propylene, and is a polymer other than the copolymer (A). By using the polymer (B), the composition has excellent flow properties such as melt tension and melt viscoelasticity, and has excellent moldability. The polymer (B) contained in the present composition may be one type or two or more types.
[0041] The branched chain preferably has a structural unit derived from propylene. The number of carbon atoms in the branched chain is preferably 500 or more, preferably 10,000 or more, more preferably 20,000 or more, and further preferably 40,000 or more, and is, for example, 200,000 or less. When the number of carbon atoms in the branched chain is within the above range, the polymer has an appropriate melt tension and strain hardening property that are excellent in moldability.
[0042] The presence or absence of a branched structure in the polymer (B) can be confirmed, for example, based on the method described in JP-A-2011-144356. The branching structure (e.g., branching index) of polymer (B) can be determined, for example, from the difference in the radius of gyration between a branched polymer and a linear polymer at the same molecular weight. In addition, for example, even in a mixture in which a branched polymer and a linear polymer are blended, the branching structure of the branched polymer can be estimated from the molecular weights of the branched polymer and the linear polymer, the radius of gyration of the mixture, and the radius of gyration of the linear polymer. For example, the radius of gyration of a mixture of a branched polymer and a linear polymer is smaller than the radius of gyration of a linear polymer of the same molecular weight. The radius of gyration can also be estimated, for example, from the intrinsic viscosity.
[0043] The polymer (B) may have a three-dimensional network structure such as a crosslinked structure, but it is preferable that the polymer (B) does not have such a three-dimensional network structure.
[0044] Examples of the polymer (B) include homopolypropylene, random polypropylene, and block polypropylene. The random polypropylene and block polypropylene include copolymers of propylene and an α-olefin having 2 and / or 4 or more carbon atoms. Examples of the α-olefin having 4 or more carbon atoms include 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, and 4-methyl-1-pentene. When the polymer (B) has a structural unit derived from a unit other than propylene, the branched chain may be a chain branched from a structural unit derived from a unit other than propylene.
[0045] The polymer (B) is preferably a random polypropylene, from the viewpoints of being able to suppress whitening, and being able to easily form a molded article having excellent laminate strength, seal strength, good appearance, and insulating properties.
[0046] The polymer (B) may be an unmodified polymer or a modified polymer (e.g., an acid-modified polymer). Examples of the modified polymer include the same polymers as the modified polyolefins described below.
[0047] The MFR of the polymer (B), measured in accordance with ASTM D1238 at 230°C under a load of 2.16 kg, is preferably 0.5 g / 10 min or more, more preferably 0.8 g / 10 min or more, and is preferably 50 g / 10 min or less, more preferably 20 g / 10 min or less. When the MFR is within the above range, a composition having excellent moldability can be easily obtained.
[0048] The weight average molecular weight of the polymer (B) measured by GPC is preferably from 50,000 to 1,000,000, and more preferably from 100,000 to 800,000.
[0049] The polymer (B) may be one obtained by synthesis using a conventionally known method (e.g., a method of synthesizing a macromonomer having a terminal double bond and copolymerizing the macromonomer with propylene or the like, or a synthesis method of melt-kneading propylene or the like in the presence of a peroxide and a crosslinking agent), or a commercially available product may be used. Examples of the commercially available product include a commercially available product having an MFR (230°C, 2.16 kg load) of 1.3 to 8.5 g / 10 min and a melting point of 156 to 157°C, and a commercially available product having an MFR (230°C, 2.16 kg load) of 2.1 to 2.3 g / 10 min and a melting point of 163°C.
[0050] The content of polymer (B) in the present composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less, relative to 100% by mass of the total of copolymer (A), polymer (B) and polymer (C). When the content of the polymer (B) is within the above range, a composition having an appropriate melt tension and excellent moldability can be easily obtained.
[0051] <Propylene-based polymer (C)> The polymer (C) is not particularly limited as long as it is a propylene-based polymer other than the copolymer (A) and the polymer (B), and may be a homopolypropylene or a copolymer of propylene and an α-olefin other than propylene having 2 to 20 carbon atoms, etc. The copolymer may be a random copolymer or a block copolymer. The polymer (C) may be an unmodified polymer or a modified polymer, such as the same polymers as the modified products of polyolefins described below. The polymer (C) contained in the present composition may be one type or two or more types.
[0052] As the polymer (C), a homopolypropylene is preferred in view of the ease of forming a molded article having excellent heat resistance, and a random copolymer of propylene and an α-olefin having 2 to 20 carbon atoms other than propylene (random propylene copolymer) is more preferred in view of the ease of forming a molded article having excellent impact properties and transparency.
[0053] In the random copolymer, the content of structural units derived from propylene is usually 90 mol% or more relative to 100 mol% in total of the structural units derived from propylene and the structural units derived from an α-olefin having 2 to 20 carbon atoms other than propylene, and the content of structural units derived from an α-olefin having 2 to 20 carbon atoms other than propylene is usually 10 mol% or less, preferably 8 mol% or less, more preferably 7.5 mol% or less, preferably 0.1 mol% or more, more preferably 0.2 mol% or more.
[0054] Examples of the α-olefin having 2 to 20 carbon atoms other than propylene include ethylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. Among these, copolymers with α-olefins having 2 to 10 carbon atoms other than propylene are preferred. Two or more of the α-olefins having 2 to 20 carbon atoms other than propylene may be used.
[0055] The melting point Tm of the polymer (C) measured by differential scanning calorimetry (DSC) is preferably 110°C or higher, more preferably 120°C or higher, even more preferably 125°C or higher, and is preferably 170°C or lower, more preferably 168°C or lower. When Tm is within the above range, the moldability, heat resistance and transparency are well balanced, and the properties as a crystalline polypropylene are good, which is preferable. The Tm is the melting point (the temperature at the apex of the melting peak) observed using a DSC measurement device when the sample is held at 200°C for 10 minutes, cooled to -20°C at a rate of 10°C / min, held at -20°C for 1 minute, and then heated again to 200°C at a rate of 10°C / min. The heat of fusion (ΔH), which is the integrated value of the fusion peak, is preferably 50 mJ / mg or more.
[0056] The isotactic pentad fraction (mmmm fraction) of the polymer (C) is preferably 90% or more, more preferably 92% or more, and further preferably 95% or more. When the mmmm fraction is within the above range, a molded article having a good balance between rigidity and transparency, and particularly excellent transparency, can be easily formed. The mmmm fraction is, for example, as described in JP 2007-186664 A, 13 This is the proportion of isotactic chains in pentad units in a molecular chain measured using C-NMR, in other words, the fraction of propylene monomer units at the center of a chain in which five consecutive propylene monomer units are meso-bonded, and can be measured by the method described in the publication.
[0057] The MFR of the polymer (C) (measured at 230°C under a load of 2.16 kg) is preferably 0.01 g / 10 min or more, more preferably 0.1 g / 10 min or more, even more preferably 0.5 g / 10 min or more, and is preferably 100 g / 10 min or less, more preferably 50 g / 10 min or less, even more preferably 20 g / 10 min or less. When the MFR is within the above range, a composition having excellent moldability can be easily obtained.
[0058] The polymer (C) can be produced by various known methods using a Ziegler-Natta type catalyst or a metallocene catalyst.
[0059] The content of polymer (C) in the present composition is preferably 20 mass% or more, more preferably 27 mass% or more, even more preferably 35 mass% or more, relative to 100 mass% of the total of copolymer (A), polymer (B) and polymer (C), and is preferably 98.5 mass% or less, more preferably 97 mass% or less, even more preferably 93 mass% or less. When the content of the polymer (C) is within the above range, a molded article having excellent transparency and mechanical properties (flexibility, rigidity, etc.) can be easily formed.
[0060] <Additives> To the present composition, additives other than the above (A) to (C), specifically, additives such as polyolefins other than the above (A) to (C) or modified products thereof, weather resistance stabilizers, heat resistance stabilizers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, nucleating agents (crystal nucleating agents), lubricants, pigments, dyes, plasticizers, antioxidants, hydrochloric acid absorbers, and antioxidants, may be blended as necessary within the scope of the present invention. These additives may be used either individually or in combination of two or more.
[0061] For example, a crystal nucleating agent may be used from the viewpoints of increasing the crystallization rate, shortening the molding cycle, increasing transparency, and adjusting rigidity. The crystal nucleating agent is preferably a substance having a nucleating effect on the propylene-based resin, and specific examples include metal salts of aromatic carboxylates, metal salts of aromatic phosphates, alditol derivatives, and metal salts of rosin.
[0062] The aromatic carboxylate metal salt is preferably pt-butylbenzoic acid aluminum. The aromatic phosphate metal salt is preferably 2,2'-methylenebis(4,6-di-t-butylphenyl)sodium phosphate or 2,2'-methylenebis(4,6-di-t-butylphenyl)aluminum phosphate. The alditol derivative is preferably a hexitol derivative or a nonitol derivative, and among them, p-methyl-benzylidene sorbitol, p-ethyl-benzylidene sorbitol, and 7,8,9-trideoxy-3,5:4,6-bis-O-[(4-propylphenyl)methylene]-D-glycero-L-gulo-nonitol are preferably used. When a crystal nucleating agent is used, the content of the crystal nucleating agent in the present composition is usually 0.01 mass % or more, preferably 0.05 mass % or more, and usually 2 mass % or less, preferably 1 mass % or less.
[0063] <Method of preparing the present composition> The present composition can be prepared by mixing the components to be blended by various known methods, for example, by mixing them with a Henschel mixer, a V-blender, a ribbon blender, a tumbler blender, a kneader-ruder, etc., or by melt-kneading them with a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc. Furthermore, granulation, pulverization, etc. may be carried out as necessary. When mixing or kneading these components, each component may be added at once or in stages.
[0064] ≪Adhesive resin composition≫ The adhesive resin composition according to the present invention contains the present composition. The adhesive resin composition may consist of the present composition alone, or may contain the present composition together with other components. The content of the present composition in the adhesive resin composition is preferably 1 to 50% by mass, and more preferably 1 to 40% by mass.
[0065] It is preferable that the adhesive resin composition contains a modified polyolefin, since this has better adhesion and compatibility with the substrate (e.g., resin) and may further improve the wettability of the surface of the resulting molded article. Specific examples of the modified polyolefin include those obtained by graft-modifying the above-mentioned copolymer (A), polymer (B) or polymer (C) with one or more polar monomers.
[0066] Suitable examples of the polar monomer include unsaturated carboxylic acids and / or derivatives thereof, such as unsaturated compounds having one or more carboxylic acid groups, esters of unsaturated carboxylic compounds having a carboxylic acid group and alkyl alcohols, and unsaturated compounds having one or more carboxylic acid anhydride groups (e.g., acid anhydrides of unsaturated dicarboxylic acids). Examples of the unsaturated moiety in these compounds include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The polar monomer is preferably an unsaturated dicarboxylic acid or an acid anhydride thereof, and more preferably maleic acid, nadic acid or an acid anhydride thereof.
[0067] The modification amount (graft amount) in the modified polyolefin is usually 0.1 mass% or more, preferably 0.2 mass% or more, relative to 100 mass% of the modified polyolefin, in order to obtain better adhesion and compatibility with the substrate, and is usually 50 mass% or less, preferably 30 mass% or less, and more preferably 10 mass% or less. The degree of modification can be controlled, for example, by appropriately selecting grafting conditions.
[0068] The method for grafting the polar monomer is not particularly limited, and any conventionally known graft polymerization method can be used, such as a solution method, a melt kneading method, etc. Specifically, for example, the copolymer (A), polymer (B) or polymer (C) is melted or dissolved in a solvent to prepare a solution, and a graft monomer is added thereto to carry out a graft reaction.
[0069] When the modified polyolefin is blended in the adhesive resin composition, the content of the modified polyolefin is preferably 40 to 90 mass %, more preferably 40 to 80 mass %, relative to 100 mass % of the adhesive resin composition. When the content of the modified polyolefin is within the above range, a composition exhibiting high adhesive strength can be easily obtained.
[0070] The adhesive resin composition is usually laminated on one or both sides of a single-layer or multi-layer substrate to form a multilayer film. Specifically, the adhesive resin composition is laminated to form a multilayer film by a method of co-extruding the adhesive resin composition and a substrate layer by a known multilayer film forming method such as a T-die film forming method or an inflation film forming method, or by providing the adhesive resin composition on a substrate previously formed.
[0071] The substrate is not particularly limited, but is preferably a substrate made of a thermoplastic resin. Examples of the thermoplastic resin include polypropylene-based resins (e.g., homopolypropylene, copolymers of propylene and a small amount of α-olefin), polyethylene-based resins (e.g., low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene), known ethylene-based polymers (e.g., ethylene-α-olefin copolymers, ethylene-ethyl acrylate copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl methacrylate copolymers, ethylene-n-butyl acrylate copolymers, ethylene-vinyl alcohol copolymers), poly-4-methyl-pentene-1, and mixtures thereof. The substrate may be surface-treated by a conventional method, and may be colored or printed.
[0072] The multilayer film can be suitably used as a surface protection film for protecting metal plates such as aluminum plates, steel plates, and stainless steel plates, and their coated plates, glass plates, synthetic resin plates, and other processing members, as well as home appliances, automobile parts, and electronic parts using these members.Specific examples of the multilayer film can be suitably used as a film used in the electronics field, such as an optical plate protection film, a lens protection film, a backgrinding tape for semiconductor wafers, a dicing tape, and a protective tape for printed circuit boards, a window glass protection film, and a baking paint film.
[0073] The adhesive resin composition can be prepared by mixing the components to be blended in the composition by various known methods, for example, by mixing them with a Henschel mixer, a V-blender, a ribbon blender, a tumbler blender, a kneader-ruder, etc., or by melt-kneading them with a single-screw extruder, a twin-screw extruder, a kneader, a Banbury mixer, etc. Furthermore, granulation, pulverization, etc. may be performed as necessary. When mixing or kneading these components, each component may be added at once or in stages.
[0074] <Pellet> The pellet according to the present invention contains the present composition or the adhesive resin composition. The shape, size, etc. of the pellets are not particularly limited and may be appropriately selected depending on the desired application. The pellets can be produced by melt-kneading each component to be blended in the present composition or the adhesive resin composition in a kneader such as a Banbury mixer, a roll or an extruder, followed by granulation.
[0075] <Molded body> The molded article according to the present invention contains the present composition or the adhesive resin composition. The molded article can be produced by molding the present composition or the adhesive resin composition by a conventional molding method, for example, a sheet (film) molding method, a blow molding method, a injection molding method, a press molding method, an extrusion molding method, an inflation molding method, an extrusion blow molding method, an injection blow molding method, a vacuum molding method, a calendar molding method, or a melt T-die casting method.
[0076] The molded article is not particularly limited, but since the present composition and the adhesive resin composition exhibit the above-mentioned effects, it is preferable that the molded article is one in which the effects can be more effectively exhibited. Specific examples of the molded article include (non-stretched) films, sheets, injection molded articles, blow molded articles, and automobile parts (e.g., automobile interior parts, automobile exterior parts). More specific examples include civil engineering and building material parts such as multi-layer hoses, tubes, decorative sheets, and flooring mats, covering materials for electric wires and cables (e.g., insulating layers, sheath layers), nonwoven fabrics, stretch films, food packaging films, packaging sheets, food packaging trays and beverage cups (obtained by thermoforming the sheets), and plastic containers (obtained by folding the sheets).
[0077] <Non-oriented film> The non-stretched film is not particularly limited as long as it is a non-stretched film, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The non-stretched film may be a single layer or a multilayer. If it is a multilayer film, at least one of the layers may be a film containing the present composition or the adhesive resin composition. In addition, if the non-stretched film is a multilayer film, all of the layers are not stretched.
[0078] The thickness of the unstretched film (total thickness if multi-layered) is preferably 5 μm or more, more preferably 10 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less. In this specification, no particular distinction is made between film and sheet, but a film usually refers to a membranous body having a thickness of less than 250 μm, and a sheet usually refers to a thin plate-like body having a thickness of 250 μm or more.
[0079] Specific applications of the non-stretched film include, for example, packaging films for packaging foods, liquids, medicines, and the like.
[0080] <Sheet> The sheet is not particularly limited, and the shape, size (thickness), etc. may be appropriately selected according to the desired application. The sheet may be a single layer or a multilayer. If it is a multilayer, at least one layer of the sheet may be a sheet containing the present composition or the adhesive resin composition. The thickness of the sheet (if it is multi-layered, the total thickness) is preferably 250 to 2000 μm, more preferably 250 to 1500 μm.
[0081] Specific uses of the sheet include, for example, packaging sheets for packaging food, liquids, medicines, etc., and containers formed from the sheet (e.g., trays, cups, and containers formed by folding the sheet).
[0082] <Injection molded products and blow molded products> The injection molded article is not particularly limited, and examples thereof include molded articles produced by injection molding into a desired shape using a conventionally known injection molding device under known conditions. The injection molded articles can be used in a wide range of applications, such as interior trim materials for automobiles, exterior parts for automobiles, housings for home appliances, and containers.
[0083] The blow molded article is not particularly limited, and examples thereof include molded articles produced by blow molding into a desired shape using a conventionally known blow molding device under known conditions. The blow molded article may be a multi-layered article, in which case at least one layer contains the present composition or the adhesive resin composition.
[0084] Specific applications of the injection molded articles and blow molded articles include, for example, food containers, beverage containers, caps, pharmaceutical containers, various other containers, daily necessities (e.g., clothing cases, buckets, washbasins, stationery such as writing utensils, containers, toys, cooking utensils, and various other cases), housings for home appliances, and automobile parts.
[0085] <Automobile interior and exterior parts> The automobile interior and exterior parts are not particularly limited, and examples thereof include automobile parts molded by injection molding or the like. Specific examples of the automobile interior parts include trim, instrument panels, and column covers, while specific examples of the automobile exterior parts include fenders, bumpers, side moldings, mudguards, and mirror covers. EXAMPLES
[0086] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples as long as the gist of the present invention is not exceeded.
[0087] <Ingredients> The following raw materials were used in the following examples and comparative examples.
[0088] [Propylene-ethylene-α-olefin copolymer (A)] The propylene-ethylene-α-olefin copolymers (A-1) to (A-2) obtained in the production examples described below were used.
[0089] [Propylene-based branched polymer (B)] Propylene-based branched polymer (B-1): Propylene branched polymer with MFR (230°C, 2.16 kg load) = 1.3 g / 10 min and melting point of 157°C Propylene-based branched polymer (B-2): Propylene branched polymer with MFR (230°C, 2.16 kg load) = 8.5 g / 10 min and melting point of 157°C
[0090] [Propylene polymer (C)] Propylene polymer (C-1): random propylene copolymer, manufactured by Prime Polymer Co., Ltd., product name: Prime Polypro F227, ethylene content = 3 mol%, MFR (230°C, 2.16 kg load) = 7 g / 10 min, melting point = 150°C, mmmm fraction = 96% Propylene-based polymer (C-2): propylene-ethylene copolymer, manufactured by ExxonMobil Chemical Corporation, trade name: Vistamaxx3000, MFR (230°C, 2.16 kg load) = 7 g / 10 min Propylene-based polymer (C-3): Propylene-1-butene copolymer, MFR (230°C, 2.16 kg load) = 7g / 10min, melting point = 83°C
[0091] [Polymers other than (A) to (C)] Olefin copolymer (D-1): Ethylene-1-butene copolymer, MFR (190℃, 2.16kg load) = 3.6g / 10min, melting point = 77℃
[0092] [Production example of propylene-ethylene-α-olefin copolymer (A-1)] Diphenylmethylene(3-tert-butyl-5-ethylcyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride prepared by the method described in JP 2007-186664 A was used as the polymerization catalyst, and methylaluminoxane (Tosoh Finechem Co., Ltd., 0.3 mmol in terms of aluminum) was used as the cocatalyst. The raw materials ethylene, propylene, and 1-butene were polymerized in a hexane solution using a continuous polymerization facility to obtain a propylene-ethylene-α-olefin copolymer (A-1).
[0093] [Production example of propylene-ethylene-α-olefin copolymer (A-2)] In a 2000 ml polymerization apparatus that had been thoroughly purged with nitrogen, 833 ml of dry hexane, 120 g of 1-butene, and triisobutylaluminum (1.0 mmol) were charged at room temperature, and the temperature inside the polymerization apparatus was raised to 60°C, and the pressure inside the system was increased to 0.33 MPa with propylene. The pressure inside the system was then adjusted to 0.63 MPa with ethylene. Next, a toluene solution in which 0.002 mmol of di(p-chlorophenyl)methylene(cyclopentadienyl)(octamethyloctahydrodibenzofluorenyl)zirconium dichloride and 0.6 mmol of methylaluminoxane (manufactured by Tosoh Finechem Co., Ltd.) in terms of aluminum were contacted was added to the polymerization apparatus, and polymerization was carried out for 20 minutes while maintaining the internal temperature at 60°C and maintaining the pressure inside the system at 0.63 MPa with ethylene, and then 20 ml of methanol was added to terminate the polymerization. After depressurization, the obtained polymerization liquid was poured into 2000 ml of methanol to precipitate the polymer, and the obtained polymer was dried under vacuum at 130°C for 12 hours to obtain a propylene-ethylene-α-olefin copolymer (A-2).
[0094] <Methods for measuring the physical properties of propylene-ethylene-α-olefin copolymer (A)> The physical properties of the resulting propylene-ethylene-α-olefin copolymers (A-1) and (A-2) were measured by the following methods. The results are shown in Table 1.
[0095] a) Composition ratio According to the method described in JP 2007-186664 A, 13 It was determined by analysis of C-NMR spectrum. In this specification, the content of structural units derived from propylene is also referred to as the "propylene content", the content of structural units derived from ethylene is also referred to as the "ethylene content", and the content of structural units derived from α-olefins is also referred to as the "α-olefin content".
[0096] b) MFR The MFR was measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238.
[0097] c) Glass transition temperature Tg, melting point Tm, heat of fusion ΔH Using a hydraulic hot press molding machine set at 190°C, the copolymer (A) was heated for 5 minutes and then molded for 2 minutes under a pressure of 10 MPa, followed by cooling for 4 minutes at 20°C under a pressure of 10 MPa to produce a sheet (test piece) with a thickness of 0.5 mm. The prepared test piece was left at room temperature for 72 hours, then cut into approximately 10 mg pieces, and the cut test piece was cooled from 20°C to -20°C at a rate of 10°C / min under a nitrogen atmosphere and held at that temperature for 5 minutes. The temperature was then increased to 200°C at a rate of 10°C / min, held at that temperature for 10 minutes, then cooled to -100°C at a rate of 10°C / min, and held at that temperature for 5 minutes. The temperature was then increased to 200°C at a rate of 10°C / min. The glass transition temperature Tg and melting point Tm were obtained from the endothermic curve when the temperature was raised for the second time. The heat of fusion ΔH was calculated from the integrated value of the crystal melting peak. In addition, when the melting point Tm and heat of fusion ΔH were not observed, it is indicated as "ND".
[0098] d) Intrinsic viscosity [η] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent.
[0099] e) Tensile modulus Using a hydraulic hot press molding machine set at 200°C, the copolymer (A) was heated for 6 minutes, and then molded for 2 minutes under a pressure of 10 MPa. Thereafter, the copolymer was cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet having a thickness of 2 mm. After 72 hours at room temperature from molding, 5A-type dumbbells as specified in JIS K 7161-2:2014 were made from the produced sheets in accordance with ASTM D638, and the tensile modulus was measured when a tensile test was carried out using the dumbbells under conditions of 23°C and a tensile speed of 50 mm / min.
[0100] f) Hardness (Shore A, instantaneous value) Using a hydraulic hot press molding machine set at 200°C, the copolymer (A) was heated for 6 minutes, and then molded for 2 minutes under a pressure of 10 MPa. Thereafter, the copolymer was cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet having a thickness of 2 mm. After 72 hours had elapsed at room temperature from molding, the Shore A hardness (instantaneous value) was measured in accordance with ASTM D2240 using a durometer hardness tester (Type A) by reading the scale immediately after contacting a pusher with a test piece consisting of three stacked sheets prepared as described above.
[0101] [Table 1]
[0102] [Examples 1 to 5 and Comparative Examples 1 to 7] The raw materials shown in Table 2 were placed in a Labo Plastomill manufactured by Toyo Seiki Seisakusho Co., Ltd. in the compounding ratio (mass%) shown in Table 2, and melt-kneaded at 200°C and 60 rpm for about 5 minutes to prepare a propylene-based resin composition.
[0103] <Methods for measuring physical properties of propylene-based resin compositions> The physical properties of the prepared propylene-based resin composition were measured by the following methods. The results are shown in Table 2.
[0104] a) MFR The MFR was measured at 230°C and a load of 2.16 kg in accordance with ASTM D1238.
[0105] b) Melt tension The propylene-based resin composition was extruded into a string shape under the following conditions using a Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. The load value of the load cell when the extruded strand was wound up by a roller via a pulley attached to the load cell was taken as the melt tension. In addition, when the melt tension was not observed, it is indicated as "ND". Set temperature: 230℃ Capillary diameter: 2.095mm Capillary length: 8.00mm Cylinder extrusion speed: 15mm / min Winding speed: 15m / min
[0106] c) Tensile modulus and breaking stress The propylene-based resin composition was heated for 6 minutes using a hydraulic hot press molding machine set at 200°C, and then molded for 2 minutes under a pressure of 10 MPa. The composition was then cooled for 2 minutes at 20°C under a pressure of 10 MPa to produce a sheet having a thickness of 2 mm. After 72 hours at room temperature from molding, 5A-type dumbbells as specified in JIS K 7161-2:2014 were made from the produced sheets in accordance with ASTM D638, and the tensile modulus and breaking stress were measured when a tensile test was carried out using the dumbbells at 23°C and a tensile speed of 50 mm / min.
[0107] d) Hardness (Shore D, instantaneous value) The propylene-based resin composition was heated for 6 minutes using a hydraulic hot press molding machine set at 200°C, and then molded for 2 minutes under a pressure of 10 MPa. The composition was then cooled for 2 minutes at 20°C under a pressure of 10 MPa to produce a sheet having a thickness of 2 mm. After 72 hours had elapsed from molding at room temperature, the Shore D hardness (instantaneous value) was measured in accordance with ASTM D2240 using a durometer hardness tester (D type) by reading the scale immediately after contacting a pusher with a test piece consisting of three stacked sheets prepared as described above.
[0108] e) Whitening resistance The propylene-based resin composition was heated for 6 minutes using a hydraulic hot press molding machine set at 200°C, and then molded for 2 minutes under a pressure of 10 MPa. The composition was then cooled at 20°C under a pressure of 10 MPa for 2 minutes to produce a sheet having a thickness of 500 μm. After 72 hours from molding at room temperature, a No. 2 dumbbell as specified in JIS K 6251 was made from the produced sheet, and the dumbbell was stretched 15 mm at a tensile speed of 50 mm / min. The hue (L value) before and after the dumbbell was stretched was measured using a spectrometer (CM-3700d, manufactured by Konica Minolta, Inc.), and the hue change (ΔL) was calculated based on the following formula. The smaller the ΔL value, the better the whitening resistance. In the whitening resistance test using the propylene-based resin composition obtained in Comparative Example 2, the dumbbell broke during the stretching, so the ΔL value could not be measured. For this reason, it is shown as ND in Table 2. ΔL = L value (after elongation) - L value (before elongation)
[0109] [Table 2]
Claims
1. A propylene-ethylene-α-olefin copolymer (A); A propylene-based branched polymer (B) other than the copolymer (A), A propylene-based polymer (C) other than the copolymer (A) and the polymer (B), A propylene-based resin composition comprising: The copolymer (A) contains a structural unit (i) derived from propylene, a structural unit (ii) derived from ethylene, and a structural unit (iii) derived from an α-olefin having 4 to 20 carbon atoms, and the total of these units is 100 mol %. The content of the structural unit (i) is 50 to 92 mol %, The content of the structural unit (ii) is 5 to 20 mol %, The content of the structural unit (iii) is 3 to 30 mol %, The propylene-based resin composition has a melt flow rate (230° C., 2.16 kg load) of 0.1 to 50 g / 10 min; The melt tension (230°C) of the propylene-based resin composition is 5 to 300 mN. Propylene-based resin composition.
2. With respect to 100% by mass of the total of the copolymer (A), the polymer (B) and the polymer (C), The content of the copolymer (A) is 1 to 40% by mass, The content of the polymer (B) is 0.5 to 40 mass %, The content of the polymer (C) is 20 to 98.5% by mass. The propylene-based resin composition according to claim 1 .
3. The propylene-based resin composition according to claim 1 or 2, wherein the polymer (B) has a melt flow rate (230° C., 2.16 kg load) of 0.5 g / 10 min or more.
4. The propylene-based resin composition according to any one of claims 1 to 3, wherein the copolymer (A) has a melting point of less than 100°C as measured by a differential scanning calorimeter, or no melting peak is observed.
5. The propylene-based resin composition according to any one of claims 1 to 4, wherein the copolymer (A) is a propylene-ethylene-1-butene copolymer.
6. The propylene-based resin composition according to any one of claims 1 to 5, wherein the polymer (C) is a homopolypropylene or a random propylene copolymer.
7. An adhesive resin composition comprising the propylene-based resin composition according to any one of claims 1 to 6.
8. A pellet comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
9. A molded article comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
10. A non-stretched film comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
11. A sheet comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
12. An injection-molded article comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
13. A blow molded article comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
14. An automobile part selected from an interior part and an exterior part, comprising the propylene-based resin composition according to any one of claims 1 to 6 or the adhesive resin composition according to claim 7.
Citation Information
Patent Citations
Resin composition and laminate using it
JP2002105259A
Propylene-based resin composition and use thereof
JP2013256670A
Polypropylene resin composition for extrusion foam molding
JP2015040213A
Exterior material for power storage device
JP2017216207A
Polypropylene film for packaging battery
JP2019085480A